The spatial and temporal distribution of elements in sediment of southern Terengganu coastal water - Syalindran Sevasamgaran
Plans are on the move to develop Terengganu as a tourism destination by the year 2015 and this will consequently set off the human population increase. It is believed that these factors could generate environmental impact in the state of Terengganu particularly the near-shore marine environment.